Exploring the Efficacy of Tongue Twisters in Enhancing Students’ Pronunciation - Salainti, Engelina; Neman, Meily Ivane Esther (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Students' ability to speak in English is a longing, but they face several obstacles to do this properly. One of the techniques that can be used to overcome the problem of speaking English is playing games, especially those related to speaking. Tongue Twister is one of the methods that can be used to improve students' pronunciation skills and their ability to speak English. Monotonous learning methods often make students bored and eventually do not have a high sense of interest in the lesson. Tongue twister can be one of the learning methods related to learning games; this method can make students feel less bored because they can learn while playing. In this study, the researcher wanted to explore more deeply how the perceptions and opinions of several students when they took part in the tongue twister challenge. The study involved 30 students at Klabat University enrolled in general English classes, who were randomly selected and who had participated in the tongue twister challenge. The results showed that almost 90% of the students were interested in this learning method.